An Analysis of Metaphors in Coldplay's A Head Full of Dreams Album - Ramadhan, Dhani Ringga; Wibowo, Hanafi (Indonesian Journal of Applied Linguistics Review, 2024)
This study analyzes metaphors in the song lyrics of Coldplay's album "A Head Full of Dreams," applying the conceptual metaphor theory by Lakoff and Johnson. Using a qualitative methodology, the research identifies 37 metaphorical expressions across the album, categorized into structural, ontological, and orientational metaphors. The findings reveal that ontological metaphors dominate (43.25%), followed by structural (35.14%) and orientational metaphors (21.61%). Metaphors in the lyrics are explored for their conceptual meanings and artistic impact, with an emphasis on themes of life and love. The study concludes that metaphors enrich the emotional depth of lyrics, drawing from cultural and experiential influences to bridge abstract and concrete concepts. This research highlights the significance of metaphors in understanding complex ideas through song lyrics and suggests broader applications of conceptual metaphor theory in analyzing other forms of artistic expressions.